Epidemiological analysis of hospitalizations for headaches in the regional health departments of Paraná, between 2019 and 2023 - Cavagnoli, Giovanna Lourenço; Messias, Emely Regina; Espindola, Vitor Dias; Queiroz, Bruno Dias; Mendes, Natalia Camila Correia; Souza, Marcelo Alves de (Headache Medicine, 2024)
Introduction: Headache is one of the most common complaints in the medical practice of neurology outpatient clinics. The treatment of headaches is in outpatient clinics, however, sometimes emergency measures or even hospitalization of the patient are necessary. Objectives: To analyze the profile of hospitalizations due to headaches in the regional health departments of Paraná in the last 5 years. Method: Descriptive ecological study, through data collection by the SUS Hospital Information System (SIH/SUS), linked to the Department of Informatics of the Unified Health System (DATASUS) in may 2024. The number of hospital admissions due to headaches in the population of Paraná from 2019 to 2023 was analyzed. The variables used were: age group, gender, race, year of hospitalization, health region, municipality, average length of stay and average value. Results: A total of 8,152 hospitalizations due to headaches were recorded in regional health departments of the state of Paraná between 2019 and 2023. Of this total, the second Metropolitan RS was the one with the highest number of hospitalizations (66.4%, 5,414), and the city of Campo Largo accounted for 3,659 cases. The year 2019 had the highest number of registrations (2,833), while in 2023, there was a drop of 50.7% compared to that year (1,397). There was a higher predominance of headaches in females (61.3%, 4,995) and white race/color prevailed (6,457). The predominant age group was 40-59 years (35%, 2,852). Regarding the average length of stay, the third RS Ponta Grossa had the highest average (4.8) and the 20th RS Toledo the lowest (1.5). Regarding the average value of hospitalizations, the second Metropolitan RS had the highest value, 706.16 reais. Conclusion: In view of the analysis, it was possible to observe that the profile of hospitalizations in Paraná in the period is characterized by female, white, age group between 40 to 59 years, led mainly by the 2nd Metropolitan RS, which had the highest average hospitalization value. Thus, this conclusion will be important for the development of public health policies for the treatment and prevention of headaches in the state.